Releasing Nanocapsules for High‐Throughput Printing of Stable Perovskite Solar Cells (Adv. Energy Mater. 34/2021). Issue 34 (9th September 2021) - Huang, Zengqi; Hu, Xiaotian; Zhao, Zhipeng; Meng, Xiangchuan; Su, Meng; Xue, Tangyue; Chi, Jimei; Xie, Hongfei; Cai, Zheren; Chen, Yiwang; Li, Lin; Song, Yanlin
Abstract : Perovskite Solar Cells In article number 2101291, Meng Su, Yiwang Chen, Yanlin Song and co‐workers design a perovskite nanocapsules ink to realize high‐throughput printing of large‐area efficient perovskite solar cells with excellent stability. The releasing effect of the perovskite nanocapsules promotes homogeneous nucleation by diffusion‐controlled growth. The printed small‐area devices and 25 cm 2 modules achieve efficiencies of 22.10% and 16.12%, respectively.